Zambia's Chinese Debt in the Pandemic Era - Deborah Brautigam; Yinxuan Wang (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2021)
Zambia's debt difficulties hit headlines in November 2020 when the country defaulted on its Eurobond payments. In August 2021 a new president, Hakainde Hichilema, took office, facing a debt burden that had never been fully transparent to Zambia's public and the world. This paper is CARI's contribution to public understanding of Zambia's Chinese debt. The authors use CARI data and research on loan disbursements and repayments to estimate Zambia's outstanding external public debt to all Chinese financiers, official and commercial: approximately US6.6 billion. This figure is more than double that of the most commonly cited figure for Chinese debt in Zambia (US3 billion).
Keywords: 330